What Recommendations should be Made Concerning Exercising with a Fever and/or Acute Infection? - McGrew, Christopher A (Evidence‐based Sports Medicine, 2007)
This chapter contains sections titled: Introduction Methods Fever and/or acute infectious disease: general considerations Myocarditis Viral hepatitis Infectious mononucleosis Conclusions Sample examination questions